MEASURING THE SWAY OF IMPERCEPTIBLE FACTORS IN SHAPING THE DISTINCT CHARACTER OF ANCIENT INDIAN ARCHITECTURE AND CITY PLANNING - Kelly, Tamara (PLANNING MALAYSIA, 2018)
In India, great obey to nature is evident in architecture, and the essence of life is fairly apparent in city planning. Human kind reflects his perception of life in architecture by locating the spaces within the dwelling in particular order to ensure great harmony with positive and negative forces of the cosmos. Modern architecture shaped by political and economic factors resulted in sameness among most of contemporary capitals or developments, ignoring farming and human needs that has caused decays in urban fabric, and resulting in high level of gas emissions in mega cities. By contrast, ancient architecture in India connects the occupants with surrounding environment and ensure harmony between humans and nature through many aspects, and scale is a great element being considered in space and city planning leading into the Mandala graph. In Indian philosophy, disproportion and detachment of mankind from nature and surrounding environment lead to disaster. Hence, the Mandala diagram addresses all the existence taking into account farming, human scale and needs. The purpose of this research is to examine the impact of intangible factors such as traditional beliefs and religions in shaping the astonishing character of Indian architecture. Furthermore, it delves ino many metaphysic theories to test their influences on evolving the Mandala diagram and the logic behind the distribution of functions within its parts.